2016
DOI: 10.1371/journal.pone.0165248
|View full text |Cite
|
Sign up to set email alerts
|

IL-12/IL-23p40 Is Highly Expressed in Secondary Lymphoid Organs and the CNS during All Stages of EAE, but Its Deletion Does Not Affect Disease Perpetuation

Abstract: BackgroundInterleukin (IL)-12 and IL-23 are heterodimers that share the p40 subunit, and both cytokines are critical in the differentiation of T helper (Th)1 and Th17 cells, respectively. Th1 and Th17 effector cells have been implicated in the pathogenesis of experimental autoimmune encephalitis (EAE), an animal model of the human central nervous system (CNS) autoimmune demyelinating disorder multiple sclerosis (MS). However, ustekinumab, a monoclonal antibody (mAb) against p40 failed to show efficacy over pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…our Ab blocking studies identified IL-12p40 as the prominent DC-produced factor driving the higher Th1 and Th17 cytokine production in the LysM Cre :Ppard fl/fl CD11b + :CD4 + T cell cocultures. These findings are consistent with past studies of EAE in bicistronic mice that express Il12b and YFP that showed higher expression of IL-12p40 in CD11b + CD11c + cells compared with other DC and CD11b + subsets in both the draining lymph node and spleen (46) and with the knowledge that IL-12p40 is crucial to the development of EAE (47). The effect of IL-12p40 on Th cell priming in EAE can be mediated through a number of cytokines including IL-12(p35/p40), IL-23(p19/p40), p40 monomer, and p40 2 (48).…”
Section: Discussionsupporting
confidence: 92%
“…our Ab blocking studies identified IL-12p40 as the prominent DC-produced factor driving the higher Th1 and Th17 cytokine production in the LysM Cre :Ppard fl/fl CD11b + :CD4 + T cell cocultures. These findings are consistent with past studies of EAE in bicistronic mice that express Il12b and YFP that showed higher expression of IL-12p40 in CD11b + CD11c + cells compared with other DC and CD11b + subsets in both the draining lymph node and spleen (46) and with the knowledge that IL-12p40 is crucial to the development of EAE (47). The effect of IL-12p40 on Th cell priming in EAE can be mediated through a number of cytokines including IL-12(p35/p40), IL-23(p19/p40), p40 monomer, and p40 2 (48).…”
Section: Discussionsupporting
confidence: 92%
“…After 4 days, 20 ng/ml IL-23 was added. After 3 additional days, cells were re-stimulated with 0.5 μg/ml plate-bound anti-CD3 and 0.5 μg/ml soluble anti-CD28 (Cravens et al, 2016). Th17 cultures had ~4000-fold increased production of IL-17 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“… 101 This was further corroborated in an EAE model with mice lacking the p40-ustekinumab target epitope. 102 However, the patients included in the ustekinumab study had a chronic disease course with long disease durations with low relapse activity. Furthermore, it is not clear whether the antibody can cross the blood–brain barrier effectively.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%